Biblical Figures in Israel's Colonial Political Theology - Rabinovich, Silvana (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book reveals and counteracts the misuse of biblical texts and figures in political theology, in an attempt to decolonialize the reading of the Old Testament. In the framework of Critical Theory, the book questions readings that inform the State of Israel's military apparatus. It embraces Martin Buber's pacifist vision and Edward Said's perspective on Orientalism, influenced by critical authors such as Amnon Raz Krakotzkin, Ilan Pappé, Shlomo Sand, Idith Zertal, and Enrique Dussel's.
Chapter 1: Introduction -- Chapter 2: Dangerous Brotherhoods: Isaac and Ishmael -- Chapter 3: - Committing Suicide with the Enemy: the Specter of Samson -- Chapter 4: - Victims and Victimizers 1: The Bible and the Shoah -- Chapter 5: - Victims and Victimizers -- Chapter 6: Organizing Pessimism. .
Keywords: Bible-Study and teaching; Middle East-Politics and government; Judaism-Doctrines.; Biblical Studies; Middle Eastern Politics; Jewish Theology